Public Reception of Makan Bergizi Gratis (MBG) Program on Social Media - Rezki Rahmawati; Dewi Nuraliah (Kirana Publisher (KNPub), 2026)
This study examines public acceptance of the Makan Bergizi Gratis (MBG) program on social media through a qualitative content analysis of 100 comments purposively collected from Instagram, Twitter/X, and YouTube (between March 2025-March 2026). Manual sentiment analysis classified comments into positive, negative, and neutral categories, followed by thematic analysis to identify dominant discourse patterns. Grounded in Agenda Setting Theory (McCombs & Shaw) and Framing Theory (Entman), findings reveal that negative sentiment dominates public discourse, characterized by institutional distrust, budget accountability concerns, potential corruption, unequal distribution, and program sustainability. Twitter/X exhibited the most critical discursive character reflecting its deliberative nature, while YouTube demonstrated a more balanced sentiment distribution. Positive comments reflect appreciation for the program's nutritional objectives, particularly in addressing stunting. This negative dominance signals a credibility gap in government communication. Transparent, two-way, and evidence-based communication strategies are therefore imperative to shift public perception and strengthen trust in MBG implementation.